Anthropometric Study of Nasal Index among the Population of Bangladeshi Santal Female - Talukder, Moumita; Das, Ripon Kumar; Chowdhury, Sagana Shahreen; Yesmin, Zinnat Ara; Banu, Laila Anjuman (Bangladesh Journal of Anatomy, 2018)
Context: The craniofacial anthropometric norms are essential for establishing the facial identity of a person. The Santal community being one of the major tribes of Bangladesh, there are few recorded data in the literature on the craniofacial anthropometry of that population. Study addressing the craniofacial anthropometry of the adult Santal females of Bangladesh can make a contribution in setting a standard of normative craniofacial anthropometric values and indices of adult Bangladeshi Santal females. Materials and methods: The study was a cross-sectional descriptive type with observational components carried out in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, between July 2012 and December 2013. The study was conducted on 100 Santal females of Sirajgonj district, Bangladesh. The nose height and the nose width were measured using physical procedure and nasal indices were calculated. Results: The nasal indices showed that nose of Bangladeshi Santal females are leptorrhine (50%), mesorrhine (42%), Hyperleptorrhine (5%) and Chamaerrhine (3%). Conclusion: The study findings depict that nose of Bangladeshi Santal females are mostly leptorrhine (50%) and mesorrhine (42%). Bangladesh Journal of Anatomy July 2018, Vol. 16, No. 2, pp. 32-37